Tetraguanidino-functionalized phenazine and fluorene dyes: synthesis, optical properties and metal coordination - Bindewald, Elvira; Lorenz, Roxana; Hübner, Olaf; Brox, Dominik; Herten, Dirk-Peter; Kaifer, Elisabeth; Himmel, Hans-Jörg (Dalton transactions, 2015)
In this work the first phenazine derivatives with guanidino substituents were prepared and their structural and electronic properties studied in detail. The guanidino groups decrease the HOMO-LUMO gap, massively increase the quantum yield for fluorescence and offer sites for metal coordination. The yellow-orange colored 2,3,7,8-tetraguanidino-substituted phenazine shows intense fluorescence. The wavelength of the fluorescence signal is strongly solvent dependent, covering a region from 515 nm in Et2O solution (with a record quantum yield of 0.39 in Et2O) to 640 nm in water. 2,3-Bisguanidino-substituted phenazine is less fluorescent (maximum quantum yield of 0.17 in THF), but exhibits extremely large Stokes shifts. In contrast, guanidino-functionalized fluorenes emit only very weakly. Subsequently, the influence of coordination on the electronic properties and especially the fluorescence of the phenazine system was analysed. Coordination first takes place at the guanidino groups, and leads to a blue shift of the luminescence signal as well as a massive decrease of the luminescence lifetime. Luminescence is almost quenched completely upon CuI coordination. On the other hand, in the case of ZnII coordination the fluorescence signal remains strong (quantum yield of 0.36 in CH3CN). In the case of strong zinc Lewis acids, an excess of metal compound leads to additional coordination at the phenazine N atoms. This is accompanied by significant red-shifts of the lowest-energy transition in the absorption and fluorescence spectra. Pentanuclear complexes with two phenazine units were isolated and structurally characterized, and further aggregation leads to chain polymers.
Gesehen am 26.05.2020